Retinal dystrophy in an individual carrying a de novo missense variant of SMARCA4. Issue 6 (11th April 2019) - Cappuccio, Gerarda; Brunetti‐Pierri, Raffaella; Torella, Annalaura; Pinelli, Michele; Castello, Raffaele; Casari, Giorgio; Nigro, Vincenzo; Banfi, Sandro; Simonelli, Francesca; ,; Brunetti‐Pierri, Nicola
Abstract: Background: Coffin–Siris syndrome (CSS) is characterized by intellectual disability, dysmorphic facial features, growth deficiency, microcephaly, and abnormalities of the fifth fingers/toes. CSS is caused by mutations in several genes of the BRG1‐associated factor pathway including SMARCA4. Methods: Whole‐exome sequencing was performed on a 14‐year‐old female individual who presented with mild intellectual disability and dysmorphic features, tooth abnormalities, and short stature. She had brachydactyly but no aplasia or hypoplasia of the distal phalanx or nail of the fifth digit. She was also found to have retinal dystrophy that has not been previously reported in CSS. Results: The individual presented herein was found to harbor a previously unreported de novo variant in SMARCA4. Conclusion: This case expands the phenotypic spectrum of CSS manifestations. Abstract : We report an individual harboring a previously unreported de novo variant in SMARCA4, who presented with mild dysmorphic features and retinopathy, which expand the phenotypic spectrum of Coffin‐Siris syndrome manifestations.